A nitrogen-doped wood-tar resin-based carbon material for supercapacitors and a method for preparing the same

CN118373402BActive Publication Date: 2026-10-27NANJING FORESTRY UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410305112.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2026-10-27
Estimated Expiration
2044-03-18

AI Technical Summary

Technical Problem

因此,为了解决以往电容炭得率低、比容量低、比表面积低的问题,仍需要做出改变

Benefits of technology

[0023](1)本发明通过交联共聚成功合成了氮掺杂木焦油树脂基炭材料,制备的炭材料与以往其他生物质焦油基炭材料相比,不仅表现出较高的比电容和优异的电化学稳定性,还有着更高的炭得率(>40%),比表面积大(>3000m2/g)。这一发明可以使木焦油变废为宝,实现木焦油高值化利用,提高了经济效益。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118373402B_ABST
    Figure CN118373402B_ABST
Patent Text Reader

Abstract

The application discloses a nitrogen-doped wood tar resin-based carbon material for supercapacitors and a preparation method thereof, and comprises the following steps: taking wood tar as a carbon source, taking a nitrogen-containing polymer precursor as a nitrogen source, and cross-linking with a small-molecule aldehyde, so that the conductivity and electron transmission capacity of the carbon material are effectively improved through heteroatom doping, and thus the electrochemical performance is improved. Nitrogen is uniformly doped on the surface of the carbon material through cross-linking and copolymerization of wood tar, the nitrogen-containing polymer precursor and the small-molecule aldehyde, the conductivity and surface wettability of the carbon material are improved, and a pseudo-capacitance is provided. Finally, the specific surface area of the material is improved through chemical activation, and the electrode material prepared has the advantages of large specific surface area, good cycle performance and excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of supercapacitor electrode material preparation, specifically relating to a method for preparing nitrogen-doped wood tar resin-based carbon material for supercapacitors. Background Technology

[0002] Wood tar is a major byproduct of charcoal, machine-made charcoal, and bamboo charcoal processing, produced in huge quantities, but currently not fully utilized, with most being used as fuel or directly emitted. Current research mainly focuses on tar cracking, but tar cracking efficiency is low, its composition is complex, and the cracking residue is large. It is understood that wood tar contains nearly a hundred organic compounds, mainly phenols. Although wood tar shares some similarities with coal tar, its complex composition, cumbersome processing, and difficulty in extracting distillation residues make it difficult to utilize. Using wood tar as a carbon source may be an effective and convenient alternative.

[0003] However, there are few patent reports on the carbonization and utilization of wood tar. For example, patent CN202011533868.X uses light fractions of bio-oil as a carbon source to prepare carbon electrodes for supercapacitors, but the prepared capacitor carbon has drawbacks such as low specific capacitance, low specific surface area, and low carbon yield. Another example is patent CN110028050A, which mixes bio-oil with a template agent to obtain a mixture, and then carbonizes this mixture in a tube furnace to obtain supercapacitor carbon material. This supercapacitor material has a low specific surface area and a low carbon yield, only 9.79%–17.36%. Therefore, to solve the problems of low yield, low specific capacitance, and low specific surface area of ​​previous capacitor carbon, further improvements are needed. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0006] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing nitrogen-doped wood tar resin-based carbon materials for supercapacitors.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: wood tar obtained by heating wood at high temperature is then removed by vacuum distillation to remove moisture;

[0008] The distilled wood tar was mixed with nitrogen-containing polymer precursors and aldehydes, and a catalyst was added. The mixture was then heated to initiate condensation and obtain phenolic resin-urea-formaldehyde resin material.

[0009] The obtained phenolic resin-urea-formaldehyde resin material was washed with deionized water and ethanol and then dried.

[0010] The dried product is calcined at high temperature in a nitrogen atmosphere to obtain wood pyrolysis tar resin-based carbonized material.

[0011] After mixing and grinding wood pyrolysis tar resin-based carbon material with an activator, high-temperature activation was carried out under a nitrogen atmosphere to obtain nitrogen-doped wood pyrolysis tar resin-based carbon material.

[0012] After grinding, nitrogen-doped wood pyrolysis tar resin-based carbon material is mixed with acetylene black and binder emulsion and then ultrasonically dispersed to obtain nitrogen-doped wood pyrolysis tar resin-based carbon material for supercapacitors.

[0013] In a preferred embodiment of the preparation method described in this invention, the wood includes one of broadleaf wood, coniferous wood, or bamboo.

[0014] In a preferred embodiment of the preparation method described in this invention, the nitrogen-containing polymer precursor includes any one of urea, melamine, cyanamide, or dicyandiamide; and the aldehyde includes any one of formaldehyde, glyoxal, or furfural.

[0015] In a preferred embodiment of the preparation method described in this invention, the molar ratio of the nitrogen-containing polymer precursor to the aldehyde is 0.5:1 to 10:1; the mass ratio of the distilled wood tar to the nitrogen-containing polymer precursor is 4:1 to 4; and the mass ratio of the nitrogen-containing polymer precursor to the aldehyde is 1 to 4:3.

[0016] As a preferred embodiment of the preparation method described in this invention, the activator and the pyrolytic wood tar resin-based carbon material are in a mass ratio of 1:1 to 1:4; the nitrogen-doped wood tar resin-based carbon material is mixed with acetylene black and binder emulsion in a mass ratio of 8:1:1, and the binder concentration is 60%.

[0017] In a preferred embodiment of the preparation method described in this invention, the dried product is calcined at a high temperature of 400–1000°C under a nitrogen atmosphere.

[0018] In a preferred embodiment of the preparation method described in this invention, the activator includes any one of potassium hydroxide, potassium carbonate, potassium oxalate, sodium carbonate, sodium hydroxide, or sodium amide, and the catalyst includes any one of hydrochloric acid or oxalic acid.

[0019] In a preferred embodiment of the preparation method described in this invention, the activation temperature is 700℃~1200℃.

[0020] In a preferred embodiment of the preparation method described in this invention, the adhesive comprises any one of PTFE, PVDF, or PMM.

[0021] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing nitrogen-doped wood tar resin-based carbon materials for supercapacitors.

[0022] Beneficial effects of this invention:

[0023] (1) This invention successfully synthesized nitrogen-doped wood tar resin-based carbon materials through crosslinking copolymerization. Compared with other biomass tar-based carbon materials in the past, the prepared carbon materials not only exhibit higher specific capacitance and excellent electrochemical stability, but also have a higher carbon yield (>40%) and a larger specific surface area (>3000m²). 2 This invention can turn wood tar from waste into treasure, realize the high-value utilization of wood tar, and improve economic benefits.

[0024] (2) The cross-linking copolymerization of wood tar, nitrogen-containing polymer precursor, and small molecule aldehydes used in this invention involves a condensation reaction before carbonization activation. This is equivalent to introducing nitrogen (provided by urea) and improving carbon yield through the condensation reaction. The method is simple, convenient, and can be applied on a large scale. The prepared nitrogen-doped carbon material has a carbon yield of up to 40%, which is higher than the 9.79% to 17.36% yield of the carbon material in patent CN110028050A. It has good economic benefits, improves the conductivity and charge transfer ability of the material, and has a mass specific capacitance (>430F / g). -1 At 1A / g -1 The current density is also much higher than that of supercapacitor carbon materials prepared from current wood tar or wood fiber raw materials (<350F / g). -1 At 1A / g -1 (current density).

[0025] (3) The nitrogen-doped carbon material synthesized by the present invention by controlling the molar ratio of nitrogen-containing precursor and small molecule aldehyde and the reaction temperature exhibits advantages such as good electrochemical performance and good cycle performance. Attached Figure Description

[0026] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:

[0027] Figure 1 The CV curves of the nitrogen-doped wood tar-based carbon material for supercapacitors prepared in Example 1 of this invention at different scan rates.

[0028] Figure 2 The GCD curves of the nitrogen-doped wood tar-based carbon material for supercapacitors prepared in Example 1 of this invention are shown at different current densities.

[0029] Figure 3 EIS impedance diagram of nitrogen-doped wood tar-based carbon material for supercapacitors prepared in Example 1 of this invention.

[0030] Figure 4 This is a rate performance diagram of the nitrogen-doped wood tar-based carbon material for supercapacitors prepared in Example 1 of the present invention.

[0031] Figure 5 The images shown are SEM and TEM images of the nitrogen-doped wood tar-based carbon material for supercapacitors prepared in Example 1 of this invention.

[0032] Figure 6 The above are the XPS spectra of the carbon materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 of this invention.

[0033] Figure 7 The XRD patterns of the carbon materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 of this invention are shown.

[0034] Figure 8 The carbon materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 of this invention are at 1 A / g -1 GCD curves at current density.

[0035] Figure 9 The GCD curves of the carbon materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 of this invention are shown at a current density of 30 mV / s.

[0036] Figure 10 The rate performance curves of the carbon materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 of this invention are shown. Detailed Implementation

[0037] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0038] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0040] Unless otherwise specified, all products in this embodiment are commercially available products.

[0041] Table 1

[0042] urea Aladdin U141075-500g formaldehyde solution Aladdin F111934-500ml coarse wood tar Shandong Runke Luyuan Bioengineering Co., Ltd. Applewood Pyridine Aladdin P141169-500ml benzaldehyde Aladdin B110464-100ml

[0043] Example 1

[0044] This invention provides a method for preparing nitrogen-doped wood tar-based carbon materials for supercapacitors:

[0045] (1) Remove moisture from the crude wood tar by vacuum distillation at 50°C for 1 hour in a rotary evaporator.

[0046] (2) Take 4g of distilled wood tar and 2ml of formaldehyde solution in a beaker, add 1.65ml of formaldehyde solution and 2g of urea and mix well. Add 1ml of hydrochloric acid and place in an oven at 100℃ to initiate condensation.

[0047] (3) After the reaction is complete, wash the product with deionized water and ethanol 2-3 times each, and then put the treated product in a dry oven at 100℃ for 12 hours.

[0048] (4) Transfer the dried product to a tube furnace and calcine it at 550°C for 1.5 hours under a nitrogen atmosphere with a heating rate of 5°C per minute to obtain carbonized material.

[0049] (5) The obtained carbonized material is mixed with potassium hydroxide at a mass ratio of 1:4, transferred to a tube furnace, and activated at 800°C for 2 hours under a nitrogen atmosphere with a heating rate of 5°C per minute to obtain nitrogen-doped wood tar resin-based carbon material.

[0050] Example 2

[0051] The difference from Example 1 is that the amount of urea added in step (2) is 1g.

[0052] Example 3

[0053] The difference from Example 1 is that the amount of urea added in step (2) is 4g.

[0054] Comparative Example 1

[0055] The difference from Example 1 is that steps (2) and (3) are omitted. The wood tar is transferred to a tube furnace and calcined at 550°C for 1.5 hours under a nitrogen atmosphere with a heating rate of 5°C per minute to obtain carbonized material. The obtained carbonized material is mixed with potassium hydroxide at a mass ratio of 1:4, transferred to a tube furnace, and activated at 800°C for 2 hours under a nitrogen atmosphere with a heating rate of 5°C per minute to obtain the carbon material of Comparative Example 1.

[0056] Comparative Example 2

[0057] The difference from Example 1 is that in step (2), urea is not added; only 2 ml of formaldehyde solution and 1 ml of hydrochloric acid are added, and the mixture is placed in an oven at 100°C to initiate the condensation reaction between wood tar and formaldehyde. After the reaction, the product is washed 2-3 times each with deionized water and ethanol, and then placed in a dry oven at 100°C for 12 hours. The dried product is transferred to a tube furnace and calcined at 550°C for 1.5 hours under a nitrogen atmosphere with a heating rate of 5°C per minute to obtain carbonized material. The obtained carbonized material is mixed with potassium hydroxide at a mass ratio of 1:4, transferred to a tube furnace, and activated at 800°C for 2 hours under a nitrogen atmosphere with a heating rate of 5°C per minute to obtain the carbon material of Comparative Example 2.

[0058] Performance characterization:

[0059] Table 2 shows the X-ray energy dispersive spectroscopy, elemental analysis, and carbon yield (mass before carbonization / mass after carbonization) results of the carbon materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2.

[0060] Table 2

[0061]

[0062] Figure 5 The images shown are SEM and TEM images of the nitrogen-doped wood tar-based carbon material for supercapacitors prepared in Example 1 of this invention.

[0063] As shown in Table 2, the carbon material prepared in Example 1 mainly contains three elements: C, N, and O, with nitrogen accounting for 1.11% of the total content of the main elements. Table 1 also shows that the condensation reaction before carbonization activation significantly improved the carbon yield.

[0064] Table 3 shows the specific surface area of ​​the materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2.

[0065] Table 3

[0066]

[0067] As shown in Table 3, the specific surface area of ​​each example was determined by the isothermal adsorption-desorption method under nitrogen at 77 K and calculated by the BET method. The carbon materials prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 all have large specific surface areas, which is attributed to the two-step method of carbonization followed by KOH activation.

[0068] Depend on Figure 6 It can be seen that the peaks of the XPS curve at 285, 400.1 and 531 eV correspond to the characteristic peaks of C1s, N1s and O1s, respectively.

[0069] Depend on Figure 7 It can be seen that the diffraction peaks exhibited by the XRD curves near 25° and 43° correspond to the (002) and (100) crystal planes of carbon, respectively. This indicates that Comparative Example 1 has a strong degree of order and microcrystalline structure. Other samples that underwent condensation before carbonization showed weaker diffraction peaks at 25°, indicating that condensation before carbonization activation increases disorder.

[0070] Electrochemical performance testing:

[0071] The sample carbons from Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 were used as electrode materials. The electrochemical properties of the carbon materials were detected on an electrochemical workstation, including cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). Mercury-mercury oxide was used as the reference electrode, a platinum mesh as the counter electrode, and the sample carbon material coated on nickel foam was used as the working electrode. The sample carbon material was connected to the test system through an electrode clamp, and 6 mol / L KOH was used as the electrolyte. The measurements were performed on a Shanghai Chenhua CHI660E electrochemical workstation.

[0072] The specific operation is as follows: Cleaning the nickel foam: Trim the nickel foam to a size of 1cm×5cm and place it in a glass container. First, add acetone and ultrasonically clean for 30min; then ultrasonically clean with 3mol / L hydrochloric acid for 30min; finally, ultrasonically clean with distilled water for 7min. Repeat the cleaning process several times until the pH is neutral, then switch to ethanol and ultrasonically clean for 15min. Finally, dry in a vacuum drying oven at 65℃ for 24h to obtain clean nickel foam.

[0073] Sample preparation: Weigh 8 mg of sample carbon, 1 mg of conductive agent acetylene black, and 1 mg of binder polytetrafluoroethylene and add them to a 2 ml centrifuge tube. Then, place the tube in an ultrasonic cleaner for ultrasonic dispersion to obtain nitrogen-doped wood tar resin-based carbon material for supercapacitors. Finally, coat the electrode material onto nickel foam, with a coating mass of 1–2 mg. The coating is applied to a 1 cm² area. 2The nickel foam was then transferred to a vacuum drying oven at 65°C for 24 hours. The dried nickel foam was then pressed into a tablet and held at a pressure of 10 MPa for 10–15 seconds. The nickel foam was weighed again, and the mass difference of the nickel foam before and after coating was calculated. The actual mass was then calculated and applied to the electrochemical property test.

[0074] Nickel foam coated with electrode material was used as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. These electrodes were inserted into a 6 mol / L potassium hydroxide electrolyte via a three-hole electrode holder. Cyclic voltammetry (CV) curves were obtained using an electrochemical workstation with voltage scan rates of 5, 10, 20, 50, and 100 mV / s. Chronopotentiometry (GCD) curves were also obtained with current densities of 0.5, 1, 5, 10, and 20 A / g. -1 As shown in Table 3, the electrochemical impedance spectroscopy (EIS) was measured in ACImpedance mode with a frequency range of 0.01 Hz to 100 kHz.

[0075] Table 4

[0076]

[0077] As shown in Table 4, all the prepared samples have excellent specific capacitance, with Example 2 having the highest specific capacitance.

[0078] Electrochemical tests were further performed on Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2. Figure 8 , Figure 9 The cyclic voltammetry and constant current charge-discharge diagrams for different examples show that Example 1 has the largest specific capacitance. Figure 10 The scaling characteristics of different examples are 59%, 67.2%, 63.6%, 64%, and 69.2%, respectively, for Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2. Figure 1 CV plots for tests at different scan rates. Figure 2 GCD plots were obtained under different current densities. Figure 3 EIS plot of electrode material, Figure 4 This is a rate performance curve of the electrode material. The CV curve shows that the scan area gradually increases with increasing scan rate, reaching its maximum at 100 mV / s while maintaining a rectangular structure, indicating good electrochemical performance. The EIS curve shows a steep slope and a small intersection point on the x-axis, indicating that the material has low internal resistance and diffusion resistance. Figure 3The small semicircle observed in the illustration indicates that the prepared electrode material has a low contact resistance in the electrolyte. The GCD diagram shows that when the current density is 0.5 A / g... -1 It has the longest charge / discharge time and the highest specific capacitance of 553.5 F / g. -1 It maintains a highly symmetrical shape. The rate characteristic diagram shows that the prepared electrode material maintains good charge and discharge performance even at high current densities.

[0079] Comparative Example 3

[0080] The difference from Example 1 is that urea in step (2) is replaced with melamine.

[0081] The experimental results showed that wood tar, pyridine, and benzaldehyde could not undergo a good condensation reaction, which prevented the experiment from proceeding.

[0082] Comparative Example 4

[0083] The difference from Example 1 is that in step (2), urea is replaced with pyridine and benzaldehyde is replaced with benzaldehyde.

[0084] Experimental results show that wood tar, pyridine, and benzaldehyde cannot undergo co-condensation, thus the target carbon material cannot be prepared.

[0085] This invention uses wood tar as the carbon source and a nitrogen-containing polymer precursor as the nitrogen source, and employs small-molecule aldehydes for crosslinking. Heteroatom doping effectively enhances the conductivity and electron transport capacity of the carbon material, thereby improving its electrochemical performance. Through crosslinking and copolymerization of wood tar, nitrogen-containing polymer precursors, and small-molecule aldehydes, nitrogen is uniformly doped onto the surface of the carbon material, improving its conductivity and surface wettability while providing pseudocapacitance. Finally, chemical activation increases the specific surface area of ​​the material, resulting in an electrode material with a large specific surface area, good cycle performance, and excellent electrochemical performance.

[0086] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A method for preparing nitrogen-doped wood tar resin-based carbon material for supercapacitors, characterized in that: include, Wood tar obtained by heating wood at high temperature is then removed by vacuum distillation to remove moisture. The wood includes one of broad-leaved wood, coniferous wood, or bamboo; The distilled wood tar was mixed with nitrogen-containing polymer precursors and aldehydes, and a catalyst was added before heating to initiate condensation and obtain phenolic resin-urea-formaldehyde resin material. The nitrogen-containing polymer precursor includes any one of urea, melamine, cyanamide, or dicyandiamide; the aldehyde includes any one of formaldehyde, glyoxal, or furfural. The molar ratio of the nitrogen-containing polymer precursor to the aldehyde is 0.5:1 to 10:1; the mass ratio of the distilled wood tar to the nitrogen-containing polymer precursor is 4:1 to 4; and the mass ratio of the nitrogen-containing polymer precursor to the aldehyde is 1 to 4:

3. The obtained phenolic resin-urea-formaldehyde resin material was washed with deionized water and ethanol and then dried. The dried product is calcined at high temperature in a nitrogen atmosphere at 400~1000℃ to obtain wood pyrolysis tar resin-based carbonized material. The activator and wood pyrolysis tar resin-based carbon material were mixed and ground at a mass ratio of 1:1 to 1:

4. The mixture was then heated to a high temperature of 700℃ to 1200℃ under a nitrogen atmosphere to obtain nitrogen-doped wood pyrolysis tar resin-based carbon material. After grinding, nitrogen-doped wood pyrolysis tar resin-based carbon material is mixed with acetylene black and binder emulsion and then ultrasonically dispersed to obtain nitrogen-doped wood tar resin-based carbon material for supercapacitors. The activator includes any one of potassium hydroxide, potassium carbonate, potassium oxalate, sodium carbonate, sodium hydroxide or sodium amino acid, and the catalyst includes any one of hydrochloric acid or oxalic acid. The adhesive includes any one of PTFE, PVDF or PMM; Nitrogen-doped wood tar resin-based carbon material was mixed with acetylene black and binder emulsion in a mass ratio of 8:1:1, with the binder emulsion concentration being 60%.

Citation Information

Patent Citations

  • Method for preparing supercapacitor carbon material by adopting bio-oil

    CN110028050A

  • Bio-oil light fraction-based bread-shaped porous activated carbon as well as preparation method and application thereof

    CN112713005A

  • Method for preparing activated carbon with high specific surface area utilizing wood tar

    CN102807216A

  • Nitrogen-containing carbon material for supercapacitosr, preparation method thereof, and supercapacitor electrode material

    CN105253871A

  • Nitrogen-hybridized mesoporous carbon and preparation method thereof

    CN111847446A